Strength classification and diagnosis: not all strength is created equal - James, L. P.; Talpey, S. W.; Young, W. B.; Geneau, M. C.; Newton, R. U.; Gastin, P. B. (Strength and Conditioning Journal, 2023)
Maximal force can be expressed across a range of conditions influenced by the external load and the time available to express force. As a result, several distinct and specific strength qualities exist. Conversely, some expressions of maximal force are similar and can be categorized as a single quality. Therefore, strength assessment systems must be sophisticated enough to isolate and measure each quality while minimizing redundant information. This article presents a contemporary, evidence-based and practical framework that reduces the many strength and speed-strength metrics into 5 distinct qualities. Alongside this, we present case examples of the application of strength diagnosis.